Anopheles dirus size and fecundity: relationship to larval density and protein accumulation. - S. Kitthawee (2018)
Anopheles dirus were reared at two different larval densities (100/pan and 400/pan) to produce two different size classes of adults. Both the wing length and fecundity of females from the two densities were significantly different (p less than 0.001). Adult size was related to larval density and protein accumulation during immature life. Egg production was also related to adult size. Consequently, larger field adults have the potential to live longer and produce more eggs. The smaller adult size associated with crowded larval development was apparently caused by space associated effect on feeding rather than by a shortage of food per se.